2000
DOI: 10.1016/s0194-5998(00)70205-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Head and Neck Cancer

Abstract: 728Increasing emphasis has been placed on chemoprevention as understanding of the genetic and molecular events of carcinogenesis has evolved. More than 1000 compounds that inhibit cancer development in vitro or in animal models have been identified, and active research is under way to determine which of these agents will be both effective and nontoxic in human beings. Currently, 13-cis-retinoic acid is the most studied chemopreventive agent against head and neck cancers. Unfortunately, this vitamin A derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…After the entire epithelial surface at risk is exposed to repeated insult by carcinogens, such as tobacco, oral cancer typically emerges as a result of those carcinogenic processes. This fact strongly supports the rationale for chemoprevention [66][67][68]. There have been a number of clinical trials to show effectiveness of chemoprevention for oral premalignant lesions [69,70].…”
Section: A Current Problems For Oral Cancer Chemopreventionsupporting
confidence: 66%
“…After the entire epithelial surface at risk is exposed to repeated insult by carcinogens, such as tobacco, oral cancer typically emerges as a result of those carcinogenic processes. This fact strongly supports the rationale for chemoprevention [66][67][68]. There have been a number of clinical trials to show effectiveness of chemoprevention for oral premalignant lesions [69,70].…”
Section: A Current Problems For Oral Cancer Chemopreventionsupporting
confidence: 66%
“…Retinoic acid is a well-known compound used to treat leukoplakia and premalignant lesions in the oral cavity [13]. Topical administration of retinoic acid to mucous membranes results in its accumulation in target cells and regulation of cellular proliferation and differentiation of epithelial tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Retinoic acid has been clearly demonstrated to be efficacious not only for retarding the growth of oral leukoplakia but also in decreasing the incidence of second primary tumors. 9 However, despite the success of retinoic acid, it was found that, once the drug was discontinued, the lesions had the potential to return. 9 Further, there are limiting toxicities of retinoic acid which make lifelong compliance difficult to ensure.…”
Section: Discussionmentioning
confidence: 99%
“… 9 However, despite the success of retinoic acid, it was found that, once the drug was discontinued, the lesions had the potential to return. 9 Further, there are limiting toxicities of retinoic acid which make lifelong compliance difficult to ensure. 9 Dry skin, conjunctivitis, mucositis, and appetite loss are a few of the more significant toxicities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation